The Influence Of Word Of Mouth And Service Quality On Customer Satisfaction At Cv. Sukahati Pratama - Muslim, Fauzan Fuadi; Lestari, Suci Putri; Risana, Dudu (Journal of Law, Social Science, and Management Review, 2025)
This study aims to determine the influence of Word of Mouth and Service Quality both simultaneously and partially on Customer Satisfaction at CV. Sukahati Pratama. The research method used is quantitative, with a sample of 100 respondents. The sampling method employed is simple random sampling. The analysis method used is multiple linear regression, with the regression equation results being Y = 7.692 + 0.383X1 + 0.212X2 + e. The research results show that Word of Mouth is classified as very good, Service Quality is classified as very good, and Customer Satisfaction is classified as very good. The test results indicate that Word of Mouth and Service Quality together have a significant effect on Customer Satisfaction. Partially, Word of Mouth significantly affects Customer Satisfaction, and Service Quality significantly affects Customer Satisfaction.